PENGARUH KARAKTERISTIK DIREKTUR UTAMA DAN KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris Pada Perusahaan BUMN yang Terdaftar di BEI Idx20 Tahun 2018-2020) - Nanda Danah Wasilah; Moh. Amin; Abdul Wahid Mahsuni (Universitas Islam Malang, 2022)
Identification of the characteristics of the president director as seen from his educational background and gender as well as the characteristics of the company as seen from the size of the board of commissioners, profitability and leverage are used to assess the factors of wider and better disclosure of social responsibility in state-owned companies listed on the Indonesia Stock Exchange in 2018- 2020. the type of method used in this research is correlative research with a quantitative approach. the population in this study was obtained from all state-owned companies listed on the Indonesia stock exchange idx 20 in 2018 until the year of this study using secondary data with an application period of 3 years. determined the sample by purposive sampling and obtained 19 companies from 28 listed companies so that the sample from 2018 to 2020 was 57 samples used in the study. management of the data obtained using the SPSS type application. The results obtained in this study can be explained that educational background has no significant effect on CSR, gender has no significant and negative effect on CSR, the size of the board of commissioners has a significant and negative effect on CSR, profitability as measured by Return On Assets (ROA) has no significant effect. on CSR and Leverage as measured by the Debt Equity Ratio (DER) has a significant and negative effect on CSR. Keywords: Educational Background, Gender, Size of the Board of Commissioners, Profitability, Leverage and Corporate Social Responsibility